LEGALITY OF SALE AND PURCHASE OF INHERITANCE OBJECTS EXCEEDING THE LEGITIME PORTIE AND WAIVER OF ABSOLUTE RIGHTS IN THE MATARAM DISTRICT COURT DECISION - Wafiy Ahmad Ardhika; Wardani Rizkianti (RADJA PUBLIKA, 2025)
This article analyzes the legality of the sale and purchase of objects inheritance that exceeds the legitimacy of portie and the waiver of absolute rights in Mataram District Court Decision Number 109/Pdt.G/2009/PN.Mtr. This research uses a normative juridical method with a statute approach and a case approach. Normatively, the sale and purchase transaction of inherited objects that violates the legitimate share (absolute share) of straight-line heirs is invalid and can be cancelled, because it is contrary to Article 913 of the Civil Code which protects the absolute rights of heirs, as well as the principle of joint ownership of inherited goods as regulated in Article 833 of the Civil Code. The act of selling without the consent of all heirs also has the potential to be null and void according to Article 1471 of the Civil Code. Nevertheless, the Mataram District Court Decision rejected the lawsuit for cancellation of the gift because the panel of judges considered the gift valid as a legal act while the testator was still alive and had not yet become an inheritance. This approach shows that the court places more emphasis on the legal formalities of gifts than on the protection of legitimate portfolios. The rejection of this lawsuit was deemed inconsistent with substantive justice, but did not eliminate the heirs' substantive rights as legitimate heirs. The plaintiff's defeat was due to the inaccuracy of the legal basis of the lawsuit, in which the plaintiff should have pursued the incorting (reduction of the gift) mechanism specified in Article 916 of the Civil Code, rather than a lawsuit for annulment.